2012
DOI: 10.4103/0976-237x.103633
|View full text |Cite
|
Sign up to set email alerts
|

Multiple compound odontomas in mandible: A rarity

Abstract: Odontomas are benign odontogenic tumors composed of enamel, dentine, and cementum and pulp tissue. They are usually clinically asymptomatic, but often associated with tooth eruption disturbances. The present study reports an unusual case of eleven odontomas in the left lateral incisor-canine region of lower jaw. A 26 years old female presented to the department of orthodontics and dentofacial orthopedics in H.P. Govt. Dental College and Hospital Shimla for the treatment of misaligned teeth. Clinical examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Perumal et al (22) observed that a 24-year-old female patient presented a considerable increase in the CxO size in a period of 5 years. An OxC of 40 mm was also reported in a 22-year-old man (20), while a CO of unusual size was reported in a 22-year-old woman (24). The previous reports coincide with the results of the present study, in which the linear regression model between odontoma size and age adjusted by the odontoma type and size variables established a statistically significant association (β=0.321, p =0.01), indicating that the older the age, the bigger the odontoma size.…”
Section: Discussionmentioning
confidence: 85%
“…Perumal et al (22) observed that a 24-year-old female patient presented a considerable increase in the CxO size in a period of 5 years. An OxC of 40 mm was also reported in a 22-year-old man (20), while a CO of unusual size was reported in a 22-year-old woman (24). The previous reports coincide with the results of the present study, in which the linear regression model between odontoma size and age adjusted by the odontoma type and size variables established a statistically significant association (β=0.321, p =0.01), indicating that the older the age, the bigger the odontoma size.…”
Section: Discussionmentioning
confidence: 85%
“…They are twice as common compared with the former. In contrast, complex odontomas are often found in the posterior mandibular region, thereby making the posterior maxilla, in our case, an unusual site of presentation 4 5. Odontomas are mostly diagnosed during the first two decades of life in the literature review by Zhuoying and Fengguo6 and the present case due to delayed presentation is the oldest reported case in the seventh decade of life.…”
Section: Discussionmentioning
confidence: 64%
“…17 In our case, compound odontome was found in the posterior region which is rare with an incidence of 54% in the region of the maxilla and 26.2% in the posterior region. 18 The absolute incidence of odontogenic tumors of the jaws varies from 0.02 to 0.1%, out of which, odontomas constitute about 22%. 19…”
Section: Discussionmentioning
confidence: 99%